Italian as the Second Language for the Study: a Didactic Path for University Students - Lo Presti, Maria Vittoria (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
Courses for foreign students that integrate linguistic and subject-specific learning represent a resource for Italian universities, as they guarantee effective learning in Italian L2 and in the subject studied. In this paper we illustrate, analyse and comment on the proposal offered by an Italian course for specific study purposes – the Esercitazioni di Linguistica generale per studenti cinesi – active at the Università Cattolica del Sacro Cuore, in order to design and share good teaching practices.